MATHEMATICAL MODELING OF METALLURGICAL ENTERPRISES HYDRO-ENERGY UTILIZATION SYSTEMS - Kovalenko, Viktor; Paziuk, Mikhailo; Yefanov PhD, Vladimir; Ovchynnykova, Iryna (Scientific Journal "Metallurgy", 2024)
To utilize the maximum amount of potential energy of the flow of secondary water, which is diverted from technological equipment, and the amount of which depends on the topology of such sources and the configuration of the collection system, it is necessary to create a mathematical model of the latter and optimize its structure and parameters. In order to predict the energy characteristics of the water flow that will flow to the hydro turbine, statistical information on the actual water consumption by the equipment in the system of the reversible cycle of the metallurgical enterprise of the Zaporizhzhia region was collected. It has been established that the condition for the creation of energy-efficient hydropower utilization systems in the conditions of industrial enterprises is the selection of their structure at the optimization level and the determination of the technical characteristics of its elements, as well as taking into account the modes and specifics of water consumption of technological units, which will depend on the energy indicators of the real total water flow entering the hydro turbine micro hydropower plant. The paper developed a mathematical model of a stochastic generator of secondary water consumption of an industrial metallurgical enterprise, which allows to more accurately determine the parameters of hydropower utilization systems. The modeling of the flow of technical water is performed taking into account the dynamic nature of water consumption for the needs of cooling technological equipment. Statistical data obtained experimentally were used to determine the distribution law of the random amount of expenditure. It has been established that experimental observations of water consumption are most accurately described by the Poisson distribution law with parameters 4,12 і k = 1...14 . For the implementation of this method, the autocorrelation function of technical water consumption is preliminarily constructed and the coefficients bk are determined by solving the system of equations. The applied approach makes it possible to create stochastic generators of secondary water consumption of any metallurgical enterprise based on their predicted values and to calculate the approximate hydropower potential of their watercourse, to select the parameters of the necessary equipment.